2017
DOI: 10.1111/mec.14352
|View full text |Cite
|
Sign up to set email alerts
|

Seascape genomics reveals fine‐scale patterns of dispersal for a reef fish along the ecologically divergent coast of Northwestern Australia

Abstract: Understanding the drivers of dispersal among populations is a central topic in marine ecology and fundamental for spatially explicit management of marine resources. The extensive coast of Northwestern Australia provides an emerging frontier for implementing new genomic tools to comparatively identify patterns of dispersal across diverse and extreme environmental conditions. Here, we focused on the stripey snapper (Lutjanus carponotatus), which is important to recreational, charter-based and customary fishers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 95 publications
(123 reference statements)
2
27
0
Order By: Relevance
“…Genome‐wide single nucleotide polymorphisms (SNPs), generated by restriction site‐associated DNA sequencing (RAD‐seq), have proven valuable for studying divergence driven by natural selection in model fishes adapted to freshwater (cichlids, Wagner et al, 2013) and euryhaline environments (threespine stickleback, Hohenlohe et al, 2010), and a number of nonmodel reef fishes (Beltrán, Schizas, Appeldoorn, & Prada, 2017; Bernal, Gaither, Simison, & Rocha, 2017; DiBattista, Travers, et al, 2017; Gould & Dunlap, 2017; Harrison et al, 2017; Picq, McMillan, & Puebla, 2016; Puebla, Bermingham, & McMillan, 2014; Stockwell et al, 2016). Using RAD‐seq technology, Gaither et al (2015) demonstrated that the strongest signals of selection in a widespread surgeonfish ( Acanthurus olivaceus ) were associated with divergent environmental conditions in a peripheral population.…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide single nucleotide polymorphisms (SNPs), generated by restriction site‐associated DNA sequencing (RAD‐seq), have proven valuable for studying divergence driven by natural selection in model fishes adapted to freshwater (cichlids, Wagner et al, 2013) and euryhaline environments (threespine stickleback, Hohenlohe et al, 2010), and a number of nonmodel reef fishes (Beltrán, Schizas, Appeldoorn, & Prada, 2017; Bernal, Gaither, Simison, & Rocha, 2017; DiBattista, Travers, et al, 2017; Gould & Dunlap, 2017; Harrison et al, 2017; Picq, McMillan, & Puebla, 2016; Puebla, Bermingham, & McMillan, 2014; Stockwell et al, 2016). Using RAD‐seq technology, Gaither et al (2015) demonstrated that the strongest signals of selection in a widespread surgeonfish ( Acanthurus olivaceus ) were associated with divergent environmental conditions in a peripheral population.…”
Section: Introductionmentioning
confidence: 99%
“…The number of SNPs is an important factor for genetic analysis because analyses with a large number of SNPs often increase the power to detect population structure, which cannot be unveiled with a limited number of molecular markers (Attard et al, 2018;Weiss, Weigand, Weigand, & Leese, 2018). This is typically the case for marine organisms, where geographically distant populations are often connected via passive larval dispersal, making it difficult to detect genetic differentiation with few SNPs (Carreras et al, 2017;DiBattista et al, 2017;Vendrami et al, 2017). Moreover, this method is expected to be tolerant to degraded DNA samples as it utilizes short amplicons.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between PLD and genetic population structure is not straightforward (Selkoe et al ., ), as a positive correlation between the two is reported in some studies (Gaither et al ., , ), but not in others (Barber et al ., ; Weersing & Toonen, ). This ambiguity suggests that larval dispersal in marine species is not only influenced by PLD but also local oceanographic current conditions (DiBattista et al ., ; Otwoma & Kochzius, ), larval behaviour (Fisher et al ., ) and historical processes (Otwoma & Kochzius, ).…”
Section: Introductionmentioning
confidence: 99%